IMPACT OF GOVERNANCE PERFORMANCE ON THE INDONESIAN MAP STANDARIDISING PROCESS - Nabiha Zain Muhamad; Raldi Hendro Koestoer (Geoplanning: Journal of Geomatics and Planning, 2018)
The lack of standardized thematic maps in Indonesia has led to many land ownerships conflicts on the ground. The problem began since Indonesia started to exploit its natural resources by giving up its management to the market in the early 1960s. Concessions to exploit natural resources were given out without adequate assessment to real potential value of the resources. Mapping of concession areas by respective ministries without any standardized method or reference lead to the production of multiple official maps that conflict one another. Efforts to standardize the conflicting maps were initiated in 2011 and is currently still ongoing. This study aims to derive governance performance indices that directly or indirectly affect the map standardizing process. This study interviewed sources related to either the policy making process at the national level; government officials executing the policy at the provincial level and those affected by the conflict and other stakeholders advocating their rights. Interviewees include a number of officials in the central government both current and when the initiative were launched, provincial government and at the village level. To achieve sustainable development in environmental management, good governance is a prerequisite. However, the study found that sectoral ego and low government performance including, among others, corruption played a big role in hindering the process. By adding governance performance indices along with natural and economic variables to a forecast model, it can be predicted when Indonesia will likely to achieve its ideal level of harmonized maps.